Theme-Based Teaching and Meaningful Learning (2018)
ABSTRACT: Nowadays, one of the biggest challenges for teachers is to be able to involve students in the classes. The aim of this action research project was to explore the impact produced on class engagement through the implementation of theme-based teaching that is tied by the interests and needs of the students. This action research was developed during two school terms with a group of fifth graders at Institución Educativa Jesus rey. Data was collected through observations, surveys, and interviews. The project shows how the use of theme-based teaching is a powerful tool to keep kids engaged in the English class and to promote meaningful learning.